Relationship among some coordinative and dynamic strength capabilities and constructive and conceptual thinking among preschool-age children - Malambo, Chipo; Klepačová, Adéla; Brodská, Kateřina; Clark, Cain Craig Truman; Musálek, Martin (Frontiers in Psychology, 2024)
Background Existing research underscores the positive influence of consistent physical activity, fitness, and motor coordination on school-aged children’s cognitive and academic performance. However, a gap exists in fully understanding this relationship among preschoolers, a critical age group where the development of cognitive functions is significant. The study aims to expand upon existing evidence that connects motor and cognitive development by examining the correlation between specific motor coordination and physical fitness skills and the development of constructive and conceptual thinking in preschool-aged children. Methods Data from 56 children aged 4–5 years (mean age 4.5 ± 0.36y), comprising 30 girls and 26 boys, participated in this study. We assessed muscular strength (via standing long jump, wall toss test, flexibility), agility (4 × 5 m shuttle), cardiorespiratory fitness (20 m pacer test), and motor coordination (lateral jumping, platform shifting). Cognitive abilities were measured using the IDS-P. Results Linear regression models showed that significant predictors of constructive thinking scores were observed solely for flexibility (p = 0.02) and shifting platforms (p = 0.01). Notably, flexibility exhibited a negative relationship (β = −1.68). In the context of conceptual thinking, significant predictors (p < 0.05) included standing long jump (p = 0.01), jumping laterally (p = 0.005), shifting platforms (p = 0.001), throwing (p = 0.02). Conclusion Coordination-demanding activities seem to be related considerably to conceptual thinking in preschoolers. Integrating such motor activities into preschool curricula that demand cognitive engagement can positively influence the development of cognitive functions.